LEGAL PROTECTION POLICY FOR PERPETRATORS OF THE CRIMINAL ACT OF DOCUMENT FORGERY CARRIED OUT BY PENAL MEDIATION IN KENDAL REGENCY - Susi Purnani, Ratih; Sulchan, Akhmad (Jurnal Hukum Khaira Ummah, 2023)
Jobs would not be able to absorb the number of job seekers from year to year continues to grow. Urgent necessities of life as the main reason for job seekers to mempeerbaiki family economy. The desire to change the fate of the quick way to create these job seekers decided to work the family land with the hope that the high salary would make their fortune and family soon changed. All the risks that exist taken without regard to the risk faced when it comes to happen forgery of documents as had been required by Act No. 39 of 2004 regarding the Placement passage and Protection of Indonesian Workers Abroad. Department of Labor Kendal in addressing complaints submitted by the public when there is a problem of falsification of documents using the mediation. The approach used in this study is a sociological juridical approach is in dealing with the issues discussed by the regulations in force then corresponds to the realities in society. The method used is descriptive qualitative. Data was collected by interviewing the parties involved in research, direct observation and recording of documents. Results from this study that the protection of pre-placement for CTKI (Indonesian Labor candidate) is in accordance with Law No. 39 of 2004 regarding the Placement passage and Protection of Indonesian Workers Abroad. Policies implemented by the Department of Labor in the face of falsification of documents by way of mediation or deliberation of the relevant parties. Needed guidance and supervision of CTKI and PPTKIS, and education for the entire community. In addition, inter-sectoral cooperation. Integrated Services One-Stop will be implemented by the Department of Labor Kendal as a form of government attention to protect its citizens who want to go abroad so that does not happen again falsification of documents.Keywords: Protection Policy Law, Penal Mediation, Department of Labor, Falsification of Documents